Dealing with the margins of law: adult sex workers' resistance in everyday life - Fassi, Marisa N. (Oñati Socio-Legal Series, 2011)
This article looks at the way sex workers in Córdoba, Argentina, have dealt with legal marginalization, focusing on their understandings and associated practices of resistance. Sex workers position in law shows the group is on the margins of law, which means that their activity is not considered to be legal but is not illegal either. Since 2000 a group of sex workers started to organize to stop the constant detentions and humiliations by police officers. The organization called AMMAR (Asociación de Mujeres Meretrices Argentinas) implied a major shift from an oppression of consciousness to a consciousness of oppression, modifying in this process the terms of their resistance from mere tactics of survival to a struggle for redefinition of their position in law and society. This article firstly explores the idea of margins of law, consciousness, power and resistance, and also describes the regulation of sex work in the city of Córdoba; secondly, it refers to sex workers experiences, perceptions and practices of resistance before the organization in relation to the police, the Judiciary, as well as with other institutions, and relates this experiences with their practices of resistance in that period; thirdly, it explains the process of organization and the way it has influenced their reflective awareness and practices of resistance, it describes as well the heterogeneity of understandings regarding law. Lastly, the Conclusion revisits the outcomes and literature to propose final reflections about dealing with the margins of law in everyday life.